MAQASHID AL-SHARIAH APPROACH IN THE STRATEGY FOR DEVELOPING HALAL TOURISM IN INDONESIA - Khairani, Aulia Febri; Wira, Ahmad; Duhriah, Duhriah (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: The halal phenomenon has evolved into a global trend that significantly influences the growth of the tourism sector. Halal tourism refers to travel activities guided by Islamic Sharia principles, encompassing all aspects of services, facilities, and tourism experiences. This study aims to examine the strategy for developing halal tourism in Indonesia through the lens of the maqashid al-syariah framework. The method used in this study is a qualitative method with a literature review approach drawn from various scholarly sources. The findings reveal that Indonesia possesses substantial potential for halal tourism development, supported by its large Muslim population and favorable government policies. However, several challenges remain, including inadequate infrastructure and the lack of comprehensive halal standardization. By applying the maqashid al-syariah principles which emphasize the preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal) the development of halal tourism is oriented not only toward economic growth but also toward sustainable social, spiritual, and environmental well-being. Keywords: halal tourism; maqashid al-syariah; islamic economics; development strategy Abstrak: Fenomena halal kini menjadi tren global yang turut mendorong perkembangan sektor pariwisata. Pariwisata halal merupakan kegiatan wisata yang berlandaskan prinsip syariah Islam, mencakup aspek layanan, fasilitas, dan aktivitas wisata. Penelitian ini bertujuan untuk menganalisis strategi pengembangan pariwisata halal di Indonesia melalui pendekatan maqashid al-syariah. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi pustaka dari berbagai sumber ilmiah. Hasil penelitian menunjukkan bahwa pengembangan pariwisata halal di Indonesia memiliki potensi besar seiring dengan dukungan demografi Muslim dan kebijakan pemerintah, namun masih menghadapi kendala seperti keterbatasan infrastruktur dan standardisasi halal. Melalui pendekatan maqashid al-syariah yang menekankan nilai hifz al-din, al-nafs, al-‘aql, al-nasl, dan al-mal pengembangan pariwisata diarahkan tidak hanya pada pertumbuhan ekonomi, tetapi juga pada kemaslahatan sosial, spiritual, dan lingkungan secara berkelanjutan. Kata Kunci: pariwisata halal; maqashid al-syariah; ekonomi syariah; strategi pengembangan.